2020
DOI: 10.1016/j.ijfoodmicro.2020.108648
|View full text |Cite
|
Sign up to set email alerts
|

Variability in yeast invertase activity determines the extent of fructan hydrolysis during wheat dough fermentation and final FODMAP levels in bread

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
26
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 40 publications
3
26
0
2
Order By: Relevance
“…The absorbance was measured at 430 nm and the content was expressed as mg of quercetin equivalent (QE) per mL of kombucha tea (mg QE/mL) 68 . The invertase activity was determined according to the method described by Laurent et al 69 . The remaining sucrose was detected by HPLC as described above.…”
Section: Methodsmentioning
confidence: 99%
“…The absorbance was measured at 430 nm and the content was expressed as mg of quercetin equivalent (QE) per mL of kombucha tea (mg QE/mL) 68 . The invertase activity was determined according to the method described by Laurent et al 69 . The remaining sucrose was detected by HPLC as described above.…”
Section: Methodsmentioning
confidence: 99%
“…(2021), [18] Kautz (2017), [19] Laurent et al. (2020), [20] Longin et al. (2020), [21] Schmidt and Sciurba (2021), [22] Struyf Laurent, Verspreet, et al.…”
Section: Strategies To Produce Low Fodmap Products and Their Current ...mentioning
confidence: 99%
“…In contrast, the degradation of higher DP fructans is slower (Nilsson et al., 1987). Nonetheless, several studies reported that ∼40%−90% of the initially present fructans in wheat flour are degraded by yeast invertase during the bread‐making process (Gélinas et al., 2016; Knez et al., 2014; Laurent et al., 2020; Longin et al., 2020; Nilsson et al., 1987; Pejcz et al., 2019; Schmidt & Sciurba, 2021; Struyf, Laurent, Verspreet, et al., 2017; Struyf et al., 2018; Ziegler et al., 2016). For example, a white wheat bread made with flour that contains ∼1.2% fructans would require only ∼30% fructan degradation to result in a bread with fructan levels below the cutoff of 0.3 g/50 g bread (considering a moisture of 40% in bread).…”
Section: Strategies To Produce Low Fodmap Products and Their Current ...mentioning
confidence: 99%
See 1 more Smart Citation
“…Dentro de las propiedades físicas del pan, el volumen es una de las más importantes (Rossmann et al, 2020). El volumen de un pan puede variar a causa de varios factores, como por ejemplo la adición de aditivos que afecten el comportamiento de los lípidos (Melis et al, 2019), y el uso de cepas de S. cerevisiae que no son específicos para su uso en panadería (Laurent et al, 2020). Otro parámetro importante en el análisis de los panes es el volumen específico, según Alvis et al (2011) y Mudgil et al (2016).…”
Section: Introductionunclassified